Identification of genes related to effects of stress on immune function in the spleen in a chicken stress model using transcriptome analysis. (August 2020) - Guo, Yujie; Jiang, Ruirui; Su, Aru; Tian, Huihui; Zhang, Yanhua; Li, Wenting; Tian, Yadong; Li, Kui; Sun, Guirong; Han, Ruili; Yan, Fengbin; Kang, Xiangtao
Highlights: 7-day-old Gushi cocks stress model was successfully constructed by adding corticosterone (CORT) 30 mg/kg basic diet for 7 days. A total of 269 CORT-induced spleen significantly differentially expressed genes were obtained by RNA-seq. HSPA8, HSPA2 and IL8L1 may play important roles in the regulation of CORT-induced stress effects on immune function. Abstract: Stress is a physiological manifestation of the body's defense against adverse effects of external environment, but the molecular regulatory mechanism of stress effects on immune function of poultry has not been fully clarified. In this study, 7-day-old Chinese local breed Gushi cocks were used as model animal, and the stress model was successfully constructed by adding corticosterone (CORT) 30 mg/kg basic diet for 7 days. The spleen transcriptomes of the control group (B_S group) and the stress model group (C_S group) was determined by high-throughput mRNA sequencing (RNA-Seq) technology, and a total of 269 significantly differentially expressed genes (SDEGs) were obtained ( P adj < 0.05, |FC| ≥ 2 and FPKM > 1). Compared with B_S group, there were 140 significantly up-regulated genes and 129 significantly down-regulated genes in C_S group. The immune/stress-related Gene Ontology (GO) terms included positive regulation of T cell mediated immunity, chemokine-mediated signaling pathway, T cell mediated immunity and so on. The SDEGs such as IL8L1, HSPA8, HSPA2, RSAD2, CCR8L and DMB1 were involved in these GO terms. Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis showed that the SDEGs participated in many immune-related signaling pathways. The immune-related genes HSPA2, HSPA8, HSP90AA1, HSPH1 and HERPUD1 were enriched in Protein processing in endoplasmic reticulum pathway, IL8L1, CXCL13L2, CCR6, LEPR, CCR9 and CCR8L were enriched in Cytokine-cytokine receptor interaction pathway. The protein-protein interactions (PPI) analysis showed HSPA8, HSPA2 and IL8L1 as key core nodes had 7 interactions and may play important roles in the regulation of CORT-induced stress effects on immune function. The data onto this study enriched the genomic study of stress effects on immune function, and provided unique insights into the molecular mechanism of stress effects on immune function, and the genes identified in this study can be candidates for future research on stress response.